Hearing preservation using topical dexamethasone alone and associated with hyaluronic acid in cochlear implantation. (May 2015) - Ramos, Bernardo Faria; Tsuji, Robinson Koji; Bento, Ricardo Ferreira; Goffi-Gomez, Maria Valeria Schmidt; Ramos, Henrique Faria; Samuel, Paola Angelica; Brito, Rubens
Abstract Conclusion: Topical dexamethasone associated with hyaluronic acid in cochlear implant surgery demonstrated a statistically significant difference in the preservation of low-frequency thresholds when compared with topical dexamethasone alone and a control group. Topical dexamethasone alone was not superior in hearing preservation when compared to the control group. Objective: To compare the effects of topical dexamethasone alone and associated with hyaluronic acid intraoperatively in hearing preservation in cochlear implantation. Methods: Eighteen severely to profoundly hearing-impaired adult patients with measurable hearing were divided into three groups preoperatively: cochlear implantation as a control group (group 1), cochlear implantation using topical dexamethasone intraoperatively (group 2), and cochlear implantation using topical dexamethasone associated with hyaluronic acid intraoperatively (group 3). Preimplant and postimplant low-frequency pure-tone averages (PTAs) were calculated from unaided audiograms at 125, 250, and 500 Hz. Results: The mean changes in the low-frequency PTA comparing postoperative against preoperative thresholds were 28.03 ± 6.77 dB in group 1, 30 ± 14.53 dB in group 2, and 7.23 ± 6.12 dB in group 3. There was statistical difference when comparing group 3 with groups 1 and 2 using one-way ANOVA (p = 0.002) followed by Scheffé post hoc test.